The Effects of Asymmetrical Guanxi Perception on Job Burnout: Task Conflict, Relationship Conflict, and Process Conflict as Mediators - Hung, Hao-Kai (Frontiers in Psychology, 2021)
In Chinese organizations, individuals benefit in many ways from having good guanxi. For employees, however, guanxi also comes with documented negative effects. Until recently, the guanxi investigated in these studies was always substantial guanxi. The negative effects of non-substantial guanxi, such as the guanxi of misunderstandings for those who lack good guanxi has not been examined. This study investigates how the existence of asymmetrical guanxi perception for an employee (i.e., when other people believe that good guanxi exists between a manager and an employee, but the employee disagrees) contributes to that employee’s job burnout through task conflict, relationship conflict, and process conflict. Data were collected for 363 employees at 10 hotels in Taiwan. Structural equation modeling results suggest that relationship conflict is the most powerful mediator affecting the relationship between asymmetrical guanxi perception and job burnout. The results provide insights for researchers interested in the mechanism of how asymmetrical guanxi perception induces employee job burnout and generates useful implications for managers charged with reducing such burnout.